INVESTIGATING THE RELATIONSHIP BETWEEN PERFORMANCE MANAGEMENT SYSTEMS AND EMPLOYEE JOB SATISFACTION IN LARGE UZBEKISTAN-BASED TECHNOLOGY FIRMS (International Educators Conference, 2025)
This study investigates the relationship between Performance Management Systems (PMS) and employee job satisfaction (JS) within large technology firms based in Uzbekistan. The primary objective is to determine how various components of PMS (goal setting, fairness of appraisal, continuous feedback) influence employee motivation and commitment. The research holds theoretical and practical significance for developing effective human resource strategies within Uzbekistan's rapidly evolving IT sector. The findings will offer recommendations to organizations on refining their PMS to optimize employee satisfaction and retention.